Analisis tentang pengembangan karir dan pendidikan dan pengaruhnya terhadap kinerja melalui variabel mediasi produktifitas pegawai pada Pondok Pesantren Riyadlul Jannah Mojokerto - Fikri Zainun Nasihin (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2022)
The objectives of this research are: 1) Analyzing career development on employee productivity. 2) Analyzing the effect of education on employee productivity. 3) Analyzing career development on performance. 4) Analyzing the effect of education on performance. 5) Analyzing the effect of employee productivity on performance. 6) Analyzing career development on performance through mediating variables of employee productivity. 7) Analyzing the effect of education on performance through the mediating variable of employee productivity. The population in this study were all employees at the Rijan Mart Unit with a total of 27 people and the M2M Indonesian Fast Food unit 20 people, the total population was 47 people. so that the sampling method is to use the census technique. Where all members of the population are sampled. data analysis tool using SmartPLS software version 3.3.7 for students. From the research results, it can be concluded as follows: 1) Career development has no effect on employee productivity 2) Education has a significant effect on employee productivity 3) Career development has no effect on employee performance 4) Education has no effect on employee performance 5) Employee productivity has a significant effect on performance employees 6) Career development has a significant effect on employee performance through employee productivity 7) Education has a significant effect on employee performance through employee productivity